Penggunaan Media Canva dalam Pembelajaran Bahasa Indonesia di MIN 2 Majene - Ikbal; Fitriati, Resti; Rustan, Nurul Azmy; Ahyadi, Nadila (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to describe the use of Canva media in Indonesian language learning at MIN 2 Majene and to understand its impact on students' activities and comprehension. This study uses a descriptive qualitative approach with research subjects consisting of fifth-grade students and teachers. Data collection techniques were carried out through observation, written tests (LKPD), student reflection questionnaires, and interviews. Data analysis techniques were conducted through qualitative data analysis with the stages of data reduction, data presentation, and drawing conclusions. The research results indicate that the use of Canva media is able to improve students' understanding, as evidenced by the increase in scores in most groups. In addition, Canva media also enhances students' engagement and learning motivation, which is evident from the high enthusiasm of students in learning activities, such as group quizzes and role playing. Reflection data shows that the majority of students feel happy, find it easy to understand the material, and have the desire to learn again using the same method. The use of Canva has proven to be effective in creating interactive, engaging learning that supports the improvement of students' learning outcomes.